Association of Energy, Macronutrients, and Fiber Intakes with Bone Health in Adolescent Athletes - Miranda, Clair Costa; de Araújo Pinto, André; de Lima, Tiago Rodrigues; Bim, Mateus Augusto; Fernandes, Romulo Araujo [UNESP]; Pelegrini, Andreia (Springer Nature, 2025)
This study investigated the association between energy and macronutrient intake and bone health in 63 adolescents of both sexes who participated in volleyball, track and field, or swimming. Bone mineral content (BMC) and density (BMD) of the total body less head (TBLH), lumbar spine (L1–L4), and femoral neck were assessed using DXA. Bone geometry parameters, including cross-sectional area (CSA), cross-sectional moment of inertia (CSMI), and section modulus, were estimated. Nutritional intake was evaluated through 24-h dietary recalls. Multiple linear regression was performed adjusting for sex, maturity, body mass index, sports discipline, and total moderate-to-vigorous physical activity (Model 1), with further adjustments for calcium intake (Model 2) and total energy intake (Model 3). Energy, protein, and total as well as fractional lipid intake (particularly monounsaturated and polyunsaturated fatty acids) were predictors of BMD at TBLH, L1–L4, and femoral neck. These associations persisted in Model 2 but were attenuated in Model 3. Total lipid intake remained a predictor of BMC at TBLH and L1–L4 across all models, whereas energy and protein intakes were associated with BMC at L1–L4 in Models 1 and 2. Femoral neck BMC was associated with energy, protein, and total lipid only in Model 2. Both CSA and CSMI showed positive associations with total lipid intake, and CSA was associated with energy and protein intakes. No significant associations were found between carbohydrate or fiber and bone parameters. This study highlights energy, protein, and lipid intake as important factors in bone health among adolescent athletes.